Heterochrony and growth rate variation mediate the development of divergent genital morphologies in closely related Ohomopterus ground beetles. Issue 1 (27th November 2020) - Terada, Karen; Nishimura, Taira; Hirayama, Akihiro; Takami, Yasuoki
Abstract: The rapid divergence of genital morphology is well studied in the context of sexual selection and speciation; however, little is known about the developmental mechanisms underlying divergence in genitalia. Ground beetles in the subgenus Ohomopterus genus Carabus have species‐specific genitalia that show coevolutionary divergence between the sexes. In this study, using X‐ray microcomputed tomography, we examined the morphogenesis of male and female genitalia in two closely related Ohomopterus species with divergent genital morphologies. The morphogenetic processes generating the male and female genitalia at the pupal stage were qualitatively similar in the two species. The male aedeagus and internal sac and female bursa copulatrix were partially formed at pupation and developed gradually thereafter. The species‐specific genital parts, male copulatory piece, and female vaginal appendix differed in the timing and rate of development. The relatively long copulatory piece of Carabus maiyasanus began to develop earlier, but subsequent rates of growth were similar in the two species. The timing of the formation of the vaginal appendix and initial growth rates were similar, but subsequent rapid growth led to a longer vaginal appendix in C. maiyasanus . Thus, substantial interspecific differences in the size of genital parts were mediated by different underlying developmental mechanisms between the sexes (i.e., a shift in the developmental schedule in males and a change in growth rate in females). These results revealed the spatio–temporal dynamics of species‐specific genital structure development, providing a novel platform for evo–devo studies of the diversification of genital morphologies. Abstract : The development of divergent male (left) and female (right) genitalia in C. maiyasanus (above) and C. iwawakianus (below) was revealed by µCT imaging. Research Highlights: The developmental basis of divergent genital morphology is poorly understood. Using microcomputed tomography, we found that heterochrony and growth rate variation contributed to divergence in male and female genitalia, respectively, in two closely related beetle species.